The Colonial Machinery's Marginalisation of Indian Women's Discourses by the Mutation of Socio-Linguistic Genes (KEMANUSIAAN The Asian Journal of Humanities, 2013)
Colonialism in general and British colonialism in particular, mutates sociolinguistic genes to suit its needs. British colonialism in India controlled and shaped the development and mutation of socio-linguistic genes both directly and indirectly. The transfer of written texts, oral narratives, and non-verbal expressions can be compared to the transfer of biological genes vertically from one generation to another and horizontally from one space to another. There are three possible situations: first, a gene may transfer as a dominant gene; second, a gene may not be transferred; third, a gene may be transferred, but only as a recessive gene. A similar situation occurred among women writers: many of them never reached the present generation, and those who did are not considered important writers because the British handed over authority only to socio-linguistically engineered Indians whose sensibilities were structured to reject all such discourses. Even during the struggle for freedom, women's issues remained fixed in remarkably similar schemes during the British period as one patriarchy confronted the other. In other words, the Indian patriarchal system, though outwardly opposed the British system, also marginalised the voices of independent women by depriving them of their livelihoods, and the British assisted in this with laws, police and discourse. Socio-linguistic engineering resembles genetic engineering in many respects, and this analogy can be used to study how the sensibilities of people are controlled.